The Ruling On Fulfilling Vows Made By Parents After Their Death Study: Comparative Jurisprudence (International Journal of Environmental Sciences, 2025)
This research is titled "The Ruling on Fulfilling a Vodah on Behalf of Parents." It aims to examine the jurisprudential rulings on fulfilling vows on behalf of parents after their death, focusing on the disagreement among the schools of thought regarding their legitimacy and obligation. The research begins with the problem of the extent to which children must fulfill vows incumbent upon parents. It relies on an analytical inductive approach, tracing the evidence of jurists from the Holy Qur’an, the Prophetic Sunnah, consensus, and analogy. The study concludes that the predominant opinion is that fulfilling a vow on behalf of parents is permissible and desirable, especially financial vows. Jurists differ on its obligation based on the type of vow and the presence of a will. It also concludes by affirming the legitimacy of vows in principle and clarifying the criteria for fulfilling them on behalf of the deceased.